2014
DOI: 10.1155/2014/878704
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation in Fine Particulate Matter Mass and Chemical Composition: The Middle East Consortium for Aerosol Research Study

Abstract: Ambient fine particulate matter (PM2.5) samples were collected from January to December 2007 to investigate the sources and chemical speciation in Palestine, Jordan, and Israel. The 24-h PM2.5 samples were collected on 6-day intervals at eleven urban and rural sites simultaneously. Major chemical components including metals, ions, and organic and elemental carbon were analyzed. The mass concentrations of PM2.5 across the 11 sites varied from 20.6 to 40.3 μg/m3, with an average of 28.7 μg/m3. Seasonal variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 75 publications
(105 reference statements)
4
20
0
Order By: Relevance
“…Results demonstrated that PM 2.5 predictability did not depend on site. While our study region covered only a limited geographic region, this result is consistent with Abdeen et al (2014) who showed that the soluble fraction of PM 2.5 aerosols did not vary greatly across three countries in the Middle East, indicating that PM 2.5 particles were similarly hygroscopic between countries.…”
Section: Discussionsupporting
confidence: 91%
“…Results demonstrated that PM 2.5 predictability did not depend on site. While our study region covered only a limited geographic region, this result is consistent with Abdeen et al (2014) who showed that the soluble fraction of PM 2.5 aerosols did not vary greatly across three countries in the Middle East, indicating that PM 2.5 particles were similarly hygroscopic between countries.…”
Section: Discussionsupporting
confidence: 91%
“…Table 1 presents some comparative values of measured EC and OC concentrations in PM 2.5 in urban areas worldwide, since urban areas are expected to share some similar anthropogenic source types (e.g., vehicular and industrial emissions) with Riyadh. The average concentrations in this work for both EC and OC were remarkably consistent with those reported by von Schneidemesser et al (2010) and Abdeen et al (2014) Zhao et al, 2013), reflective of the different mix of sources and different photochemical environments. EC concentrations also vary widely among urban regions, depending on the characteristics of local sources.…”
Section: Overview Of Ec and Oc Concentrationssupporting
confidence: 91%
“…Tsiouri et al (2015) summarized the major sources of PM 10 in ambient air in the Middle East as oil combustion, resuspended soil, road traffic, crustal dust, and marine aerosol; significant sources of PM 2.5 were oil combustion in power plants, resuspended soil, sand dust, and road traffic. Carbonaceous particles were estimated to account for 50-60 % of PM 2.5 in cities in the State of Palestine, Jordan, and Israel (Abdeen et al, 2014). Not surprisingly, since oil production and processing was widespread across the Middle East, heavy oil combustion was estimated to contribute 69 % to PM 2.5 mass and 18 % to PM 10 in Jeddah, Saudi Arabia (Khodeir et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To obtain particle density, also information about chemical composition and agglomeration state (e.g., fractal dimension) is needed. Abdeen et al [52] estimated The shape of the mean particle size distributions were relatively similar among the four areas we considered in Amman; the only difference was in the total concentration, which was the highest on main roads, followed by the downtown area and then by the urban background location (University of Jordan campus and its surroundings). If size-resolved particle densities are known, the particle mass size distribution can be calculated by assuming spherical particles.…”
Section: Particle Size Distributionsmentioning
confidence: 80%